A quantitative method to evaluate the effect of xylanases in baking - Stinson, Jesse (Kansas State University, 2012)
β-(1,4)-endoxylanases, commonly referred to as xylanases, have become integral to the industrial breadmaking process. This enzyme is known to cause improvement in dough rheology, loaf volume, and crumb grain. Significant research has been conducted regarding the structure, function, and inhibition of xylanases, but there is currently no quick and reproducible method to evaluate their effect in baking. The goal of this research was to develop a quantitative method for this purpose and to determine why the effect of xylanases varies with different wheat flours. The currently used methods of test baking, dough stickiness, and spectrophotometric analysis for reducing sugars were evaluated, and failed to provide reproducible results. Therefore, a new method was developed to measure the Flour Water Expression Rate (FWER) with the addition of xylanases. Commercially available enzymes from Aspergillus niger and Bacillus subtilis were evaluated in this study. The FWER method measures the amount of water released by the xylanase over a set period of time. This method consistently provided statistically significant data (p<0.05), which was able to provide a comparison of xylanases from A. niger and B. subtilis in different flours. The results indicated that the xylanase from A. niger tends to release more water, have a higher FWER value, than the xylanase from B. subtilis. In one flour, A. niger xylanase resulted in an FWER of 15.18 compared to B. subtilis xylanase that resulted in an FWER of 9.57 at equivalent activities. However, inhibitors in the wheat appeared to cause an impact on the FWER, which was evaluated with an uninhibited xylanase from B. subtilis. This new method for the evaluation of xylanases in baking suggests varying levels of xylanase inhibitors in wheat may be the reason xylanases effect wheat flours differently.
Keywords: Xylanase; Arabinoxylan; Breadmaking; Food Science (0359)